EFEKTIVITAS PEMBELAJARAN DARING DALAM MENINGKATKAN KECAKAPAN TEKNOLOGI DAN KELEKATAN ORANG TUA DENGAN SISWA SEKOLAH DASAR - Masluhah, Masluhah; Udhmah, Syafaatul; Isnaini, Nur Fajriyatul; Lailiyah, Siti (AULADUNA: Jurnal Pendidikan Dasar Islam, 2022)
Abstract The Covid-19 pandemic has switched the face-to-face learning system to online learning related to digital technology access and the parent-student attachment to learning activities. This study aimed to explain the effectiveness of online learning on technology ability and parent attachment in elementary school students. The method used was a quantitative survey. The sampling technique was random sampling with 396 total population, and 40 participants were students’ parents at MI Islamiyah Ngoro Jombang. The data were collected using a questionnaire. The data analysis used descriptive statistical tests and manova (multivariate analysis of variance). The results indicated that 13 students took online learning (X) for less than 1 year and 27 students for more than 1 year. This result proved that online learning significantly influenced technology ability and parent-student attachment. Therefore, it can be concluded that online learning effectively improved technology skills and parental attachment to students at MI Islamiyah Ngoro Jombang.